The Study Of Chlorophyll- Content By Using Aqua Modis Satellite Imagery In Marinewaters Of Rokan Hilir Regency Riau Province - Raja Siagian; Joko Samiaji; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from October until December 2013 at marinewaters of Rokan Hilir Regency Riau Province. The purpose of this research was toinvestigate the chlorophyll- content using Aqua MODIS satellite image whichwas presented in the form of a map. The method used was case study method. Theresults showed the chlorophyll- concentrations were not varied greatly. InOctober and November 2013 the lowest values were 0,71 l and 0,69 mg/lrespectively, whereas the highest value in both months was 1,73 mg/l. Thechlorophyll- values in December 2013 ranged from 0,77-1,91 mg/l. The studyfound that the high values of cholophyll- in general were shown increasingtowards the coastal areas.Key words : Chlorophyll- , Aqua MODIS and Rokan Hilir Regency